Stroke prevention in patients with atrial fibrillation and chronic hepatic disease - Varela, Flávia Alexandra Costa (2018)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2018